ANALISIS PELAKSANAAN PERENCANAAN REKRUTMEN KARYAWAN DI MUSEUM PUSAKA NIAS KOTA GUNUNGSTOLI - Sadarman Laia; Odalioziduhu Halawa; Ayler Beniah Ndraha (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. Implementation planning is everything that is prepared from the start before the activity or activities will be carried out to achieve certain goals. The problem in this research is that the implementation of employee recruitment planning at the Nias Heritage Museum was not analyzed or not predicted correctly, looking at the pluses and minuses of employee recruitment, where they did not carry out health tests, did not carry out intelligence tests and did not schedule announcements of accepted or rejected results. The aim of this research is to: 1) Understand the implementation of employee recruitment planning at the Nias Heritage Museum, Gunungsitoli City. 2) Knowing the procedures for implementing employee recruitment planning at the Nias Heritage Museum, Gunungsitoli City and 3) Knowing the obstacles to implementing employee recruitment planning at the Nias Heritage Museum, Gunungsitoli City. The theory used in this research uses the concept of Sri Budi Cantika Yuli quoted by Reinaldi Irvan (2014). The type of research used is qualitative research. The informants in this research were the Director and HRD of the Nias Heritage Museum who carried out observations, interviews and documentation as well as data analysis by reducing data, presenting data and drawing conclusions. The conclusion of this research is that the implementation of employee recruitment planning at the Nias Heritage Museum has not been optimal, where the implementation of employee recruitment planning is only carried out by determining the number and qualifications, aptitude tests, interviews and filling out application forms and assessing whether the results are accepted or rejected using procedures for setting goals in recruitment planning. employees reported to the Trustees of the MPN Foundation, determining recruitment requirements in accordance with Article 12 of the requirements for accepting employees of the Nias Heritage Museum, implementing employee recruitment planning adjusted to needs, implementing employee recruitment planning adjusted to skills, experience and education, determining recruitment time, determining costs, conducting evaluations employee recruitment planning and experiencing obstacles where assessing prospective employees does not match the expected skills and lack of exploring information and potential possessed by prospective employees which results in work results not being optimal. So this needs to be evaluated regarding the needs and qualities of those who will be recruited by the Nias Heritage Museum.